Nuclear density determination and the purification of wild type Neurospora nuclei using Percoll gradients. - K. Talbot; P. J. Russell (Fungal Genetics Reports, 1980)
Nuclear density determination and the purification of wild type Neurospora nuclei using Percoll gradients.